Systematic Literature Review: Mathematical Literacy Skills in Terms of Mathematics Learning Motivation - Meti, Meti Hamdiyanti; Rodiana , Ivta; Laelasari , Laelasari; Subroto , Toto (Universitas Islam Indonesia, 2024)
Mathematical literacy and motivation to learn mathematics are two important aspects of education. Mathematical literacy enables students to understand and apply mathematical concepts in everyday life, as well as think logically and solve problems. Mathematics learning motivation influences students' effort and perseverance in learning the material, improving academic interest and performance. The combination of the two is essential for educational success and the development of critical thinking skills required in the modern world. The objectives of research generally cover the following aspects Measuring Mathematics Literacy Level, Assessing Mathematics Learning Motivation, Identifying the Relationship between Mathematics Literacy and Learning Motivation, Recognizing Barriers and Challenges, Developing Effective Learning Strategies. This research uses the SLR (Systematic Literature Review) method by reviewing 16 articles. Data collection in this study was carried out by reviewing all articles related to Mathematical Literacy Ability, Learning Motivation, Mathematical Literacy Ability in terms of Learning Motivation published from 2019 to 2023. Based on the results of the study, it was found that motivation to learn mathematics plays an important role in students' mathematical literacy skills. Students with low motivation tend to learn by force, so their mathematical literacy skills are low because they tend to do problems procedurally without in-depth analysis. The implication is the need for motivational strategies, curriculum design, teacher training, literacy programs, and parental involvement.